2017
DOI: 10.17306/j.afs.0497
|View full text |Cite
|
Sign up to set email alerts
|

The influence of microwave cooking on the nutritional composition and antioxidant activity of the underutilized perah seed

Abstract: Perah (Elateriospermum tapos) seed is a type of seed that can be easily grown and is found in abundance, especially on the east coast of Malaysia and in southern Thailand. The perah fruits are about 2-2.5 in long, oblong, buff in colour and suffused pink on the exposed side, hanging singly on a stalk 1-6 in long. ABSTRACTBackground. Perah seed is one of the most underutilized oilseeds, containing high nutritional values and high percentage of α-linoleneic acid, which may have a high potential in food and phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Moreover, variations in the cooking conditions, such as maximum temperature reached, cooking time, pH, surface/volume relation, water used, oxygen and light presence, matrix and/or food type, as well as compounds sensitivity to these factors can influence the final composition [26,27]. Some research works have been conducted on the analysis of nutritional and phytochemical composition, as well as antioxidant activity of traditionally consumed wild edible plants all over the world [28][29][30][31][32][33][34][35][36][37][38]. For example, Trichopoulou et al [28] reported data of the nutritional composition of Cretan pies elaborated with cultivated and wild vegetables (such as Rumex spp.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, variations in the cooking conditions, such as maximum temperature reached, cooking time, pH, surface/volume relation, water used, oxygen and light presence, matrix and/or food type, as well as compounds sensitivity to these factors can influence the final composition [26,27]. Some research works have been conducted on the analysis of nutritional and phytochemical composition, as well as antioxidant activity of traditionally consumed wild edible plants all over the world [28][29][30][31][32][33][34][35][36][37][38]. For example, Trichopoulou et al [28] reported data of the nutritional composition of Cretan pies elaborated with cultivated and wild vegetables (such as Rumex spp.…”
Section: Introductionmentioning
confidence: 99%